# Find the distance from the point (-5,6) to the origin.

### 2 Answers | Add Yours

To find the distance of the point (-5, 6) from the origin .

We know that the distance d between the two points (x1,y1P and (x2,y2) is given by:

d = sqrt{(x2-x1)^2 +(y2-y1)^2}.

Therefore the distance between (-5, 6) and the origin (0,0) is given by:

d = sqrt{(0- -(5))^2+((0-6)^2} .

d = sqrt{25+36}.

d = sqrt (61}.

We'll form a right angle triangle, whose hypotenuse is the distance from origin to the point and one cathetus is its abscisa and the other cathetus is the ordinate.

We'll note the distance as r:

r = ? units.

We'll note the abscisa as x:

x = -5 units

x^2 = 25 square units

We'll note the ordinate as y:

y = 6 units

y^2 = 36 units

We'll calculate r using Pythagorean Theorem:

r^2 = x^2 + y^2

r^2 = 25 + 36

r^2 = 61

**r = sqrt 61**

**r = 7.81 units approx**

**We'll reject the negative solution since the distance is always positive**